THE ANCIENT CISTERN IN KARSHI CITY AS A HISTORICAL SOURCE - Samarov Fakhriddin (Scholar Express Journal, 2025)
This article discusses the attention paid to historical and architectural structures built in the distant past in our country during the years of independence and their importance in educating young people in the spirit of patriotism and restoring them to their original form. The topic is analyzed on the example of an old cistern in the city of Karshi.
Keywords: Karshi; Shahrisabz; mosque; mausoleum